A systematic mapping review of animal-assisted therapies for adults with Alzheimer's disease and related dementias: implications for occupational therapy - Rose, Michelle, author; Wood, Wendy, advisor; Hooper, Barbara, committee member; Bruemmer, Jason, committee member (Colorado State University. Libraries, 2016)
The objective of this thesis was to map the current state of knowledge of animal-assisted therapies (AAT) for people with Alzheimer’s disease and related dementias (ADRD) and to derive implications for occupational therapy in addressing dementia-specific quality of life (QoL). This study located 13 peer-reviewed articles related to AAT for adults with ADRD. These articles were written in English, published between 2004-2014, primary sources, and described a health professional as either designing or providing AAT. A data extraction tool was used to record data on the health professionals, participants, interventions, outcomes, and theories. All 13 articles described an outcome related to dementia-specific QoL, hence confirming that the AAT literature addresses QoL for adults with ADRD. Furthermore, 85% of these articles mentioned interventions that were activity-based, thus empathizing that activities, or occupations, may elicit positive outcomes related to QoL. These findings suggest that using animals in therapy may facilitate positive change. These results were also easily “mapped” on to a widely adopted and influential model in occupational therapy, the Person-Environment-Occupation Model. Therefore, incorporating animals into intervention plans in occupational therapy offers a promising avenue for addressing QoL for this population.